(untitled) - Krauss, Jane (Thousand Oaks, Calif., 2013)
This timely and practical book shows how to implement academically-rich classroom projects that teach the all-important skill of inquiry.
Dạy học Tiếng Anh qua nhiệm vụ và dự án
Keywords: Phương pháp dự án trong dạy học,Project method in teaching